2017
DOI: 10.7196/ajhpe.2017.v9i3.828
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the educational environment of physiotherapy students at the University of Rwanda using the Dundee Ready Educational Environment Measure (DREEM)

Abstract: An educational environment (EE) is made up of three major compo nents: the physical environment, the emotional climate and the intellectual climate. [1] The EE of professional health training is mainly determined by the interactions between different stakeholder groups and the organisational structures of the environment. [2] Ideally, the EE should foster intellectual activities and academic progression, while simultaneously encouraging friendliness, cooperation and support. It is important to get students' fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
1
2
0
1
Order By: Relevance
“…The quantitative results were corroborated by the qualitative ones, and these highlighted some specific issues that need to be addressed. For instance, the quantitative finding that the social domain had the lowest perception score (14.58/28), and which was consistent with results from other similar studies (13,23), was confirmed by the qualitative findings. During the interviews, it appeared that the most overwhelming challenge for the students in general was the overpopulation in the students' rooms as mentioned by all the interview participants.…”
Section: Lecturerssupporting
confidence: 91%
See 1 more Smart Citation
“…The quantitative results were corroborated by the qualitative ones, and these highlighted some specific issues that need to be addressed. For instance, the quantitative finding that the social domain had the lowest perception score (14.58/28), and which was consistent with results from other similar studies (13,23), was confirmed by the qualitative findings. During the interviews, it appeared that the most overwhelming challenge for the students in general was the overpopulation in the students' rooms as mentioned by all the interview participants.…”
Section: Lecturerssupporting
confidence: 91%
“…Although several studies have explored the strengths and weaknesses of EEs around the world (4,6,(8)(9)(10)(11)(12), there is very limited information relevant to the UR. A recent study (13) explored the perception of the EE in the UR, but it was limited to physiotherapy students only. Also, as it used a quantitative descriptive approach only, it did not provide participants with opportunities to tell their stories outside the boundaries of structured measurement scales, and so to describe more deeply their views about their EE.…”
Section: Introductionmentioning
confidence: 99%
“…The questionnaire has been widely used in high- and middle-income countries and it has been validated (face validity was confirmed and content validity ratio was found to be 0.39) and has internal consistency reliability of 0.91 (Cronbach's alpha) 2 , 11 , 12 . Recently, few studies in the low-income countries in Africa have used this tool to assess learning environment of undergraduate students 13 , 14 . It has 50 statements which are rated on a five-point Likert scale – the lowest score is 0 which represents “strongly disagree” while the highest score is 4 representing “strongly agree”.…”
Section: Methodsmentioning
confidence: 99%
“…Diferentes investigaciones concluyen que un ambiente educacional clínico positivo es necesario para motivar el aprendizaje de los estudiantes, ya que puede influir en su participación, satisfacción y logros académicos (Bloomfield & Subramaniam, 2008;Schönrock-Adema, 2012). El ambiente educacional ha sido reconocido como un factor para lograr alta calidad, especialmente para los estudiantes de profesiones sanitarias en transición hacia etapas prácticas (Tsai et al, 2014;Cassar, 2004;Holt et al, 2004;Urimubenshi et al, 2017).…”
Section: Figura 1 Factores Que Influencian El Aprendizajeunclassified